2019
DOI: 10.1016/j.molcel.2019.01.033
|View full text |Cite
|
Sign up to set email alerts
|

P-TEFb Activation by RBM7 Shapes a Pro-survival Transcriptional Response to Genotoxic Stress

Abstract: Summary DNA damage response (DDR) involves dramatic transcriptional alterations, the mechanisms of which remain ill defined. Here, we show that following genotoxic stress, the RNA-binding motif protein 7 (RBM7) stimulates RNA polymerase II (Pol II) transcription and promotes cell viability by activating the positive transcription elongation factor b (P-TEFb) via its release from the inhibitory 7SK small nuclear ribonucleoprotein (7SK snRNP). This is mediated by activation of p38 MAPK … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 84 publications
7
68
0
Order By: Relevance
“…In this study, we provide quantitative insights into the molecular processes underlying the major transcription-coordinated cellular response that is activated in human cells upon genotoxic stress [25][26][27]34,35,37 . The establishment of precise maps of chromatin state helped us to query in detail the impact of transcription on DNA repair activities at important functional regions, including PROMPT and eRNA loci.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we provide quantitative insights into the molecular processes underlying the major transcription-coordinated cellular response that is activated in human cells upon genotoxic stress [25][26][27]34,35,37 . The establishment of precise maps of chromatin state helped us to query in detail the impact of transcription on DNA repair activities at important functional regions, including PROMPT and eRNA loci.…”
Section: Discussionmentioning
confidence: 99%
“…3). Interestingly, a growing number of studies have reported data to suggest that (i) UV irradiation preferentially inhibits elongation, rather than transcription initiation [25][26][27]34 , (ii) P-TEFb and NELF are important regulators of UV response 35,37,61 , and (iii) although elongation gradually decelerates due to the encounter of Pol II with DNA lesions, significant initiation/early elongation activity is observed in the first thousand bases of actively transcribed regions 25,26,34 , a characteristic that has also been used for the identification of active TSSs genome-wide after UV 27 . These features are consistent with our finding that new Pol II molecules are constantly recruited to PICs post-UV (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p38α pathway can also facilitate the survival of stressed cells through the MK2-mediated phosphorylation of NELFE 105 or RBM7 (ref. 106 ), which enables a RNA polymerase II transcriptional response including genes required for telomere maintenance or DNA repair.…”
Section: P38α Substrates and Functionsmentioning
confidence: 99%
“…For instance, disrupting 7SK snRNP in cardiomyocytes results in upregulation of global gene expression, leading to cardiac hypertrophy [44]. Many stresses such as UV light, heat, inhibition of transcription, and specific intracellular signaling cascades release P-TEFb from the 7SK snRNP [15,20,126,127]. Also, small compounds such as histone deacetylase inhibitors (HDACis), which include tricostatin A and suberoylanilide hydroxamic acid (SAHA); PKC agonists; bromodomain and extra-terminal (BET) bromodomain inhibitors (BETis); DNA damage-inducing agents; a strong cell-differentiation inducer, hexamethylene bisacetamide (HMBA); and others also release P-TEFb from 7SK snRNP via various known and unknown mechanisms and activate transcription elongation mediated by P-TEFb [14,15,60,[128][129][130][131][132] (Figure 2).…”
Section: Regulation Of P-tefb Functions In Cellsmentioning
confidence: 99%